Effect of a Temperature Mode of Radiation-thermal Sintering the Structure and Magnetic Properties of Mn-Zn-ferrites - V.G. Kostishyn; A.S. Komlev; M.V. Korobeynikov; A.A. Bryazgin; V.I. Shvedunov; A.V. Timofeev; M.A. Mikhailenko (Журнал нано- та електронної фізики)
2000NM Mn-Zn-ferrites have been produced by radiation-thermal sintering (RTS). We have studied the effect of RTS on the electromagnetic properties of ferrites. X-ray diffraction have been used to investigate general aspects of phase transformations during the radiation-thermal sintering of green compacts.